Financial Management of Fauziah Yarsi Mataram Integrated Islamic Elementary School from a Sharia Perspective - Ramlah Budiarti; Armiani Armiani; Baiq Reinelda Tri Yunarni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify the accountability and transparency of sharia financial management in non-profit organizations, especially SD IT Yarsi Mataram, so that the implementation of financial management can be carried out in accordance with sharia principles. This study is a literature study, where relevant solutions to the conditions that occur at SD IT Yarsi Mataram are compiled based on relevant references that can be collected. Accountability and transparency of financial management have specifically been explained in Surah Al Baqarah Verse 282. Accountability in Islam is closely related to Amanah. And the transparency of financial management will affect the level of management accountability to stakeholders. SD IT Yarsi Mataram in recent years has not been transparent about financial management. The lack of transparency efforts in the allocation of funds obtained from student guardians as stakeholders and school committee bodies, has the potential to reduce the level of accountability of financial management. This minimal transparency and low level of accountability can trigger turmoil and distrust of stakeholders over the performance of school management. By conducting financial management transparency as part of accountability to stakeholders, it will increase trust and assessment of school management performance.